ANMCO POSITION PAPER: Timing of coronary angiography in non-ST-segment elevation acute coronary syndromes. (26th August 2021) - Murrone, Adriano; di Uccio, Fortunato Scotto; Amodeo, Vincenzo; Aspromonte, Nadia; Caldarola, Pasquale; Casella, Gianni; Cipriani, Manlio; De Luca, Leonardo; Di Lenarda, Andrea; Domenicucci, Stefano; Francese, Giuseppina Maura; Imazio, Massimo; et al.
Abstract: The European Society of Cardiology guidelines on non-ST-elevation acute coronary syndromes suggest different temporal strategies for the angiographic study depending on the risk profile. The scientific evidence underlying the guideline recommendations and the critical issues currently existing in Italy, that often do not allow either an extended strategy of revascularization within 24 h or the application of the principle of the same day transfer from a spoke to a hub centre, are analysed. The position paper focuses, in particular, on the subgroup of patients with a defined diagnosis of non-ST-elevation myocardial infarction by proposing a timing of coronary angiography/revascularization that takes into account the available scientific evidence and the organizational possibilities of a considerable part of national cardiology services.